Food safety and ICT traceability systems: Lessons from Japan for developing countries - Sununtar Setboonsarng; Jun Sakai; Lucia Vancura (Asian Development Bank Institute (ADBI), 2009)
The increasing number of food safety problems occurring worldwide in recent years has heightened consumers' food safety awareness and has caused public distrust of the increasingly complex and globalized food production and trading system. Establishing a food traceability system could improve consumers' confidence and address the documentation requirements required under multinational and bilateral trade agreements. Food traceability systems are therefore becoming critical for the food industry and the public sector, as well as for consumers. The increased requirements for documentation and reporting systems are taking a toll on developing countries that are hoping to expand their trade in food or break into new markets. Smallholder farmers in particular could be further marginalized from the global food trading system by the burden of the reporting requirements. This paper reviews experiences in using information and communications technology (ICT) to create efficient traceability systems and make information more easily available to consumers. Case studies from Japan, where the use of ICT in food traceability systems is relatively advanced, reveal lessons for developing countries. The paper examines institutional arrangements, hardware and software requirements, costs of operation, roles of the public and private sectors, and the impacts of two food traceability systems (one for dried shiitake mushrooms, the other for poultry products, both by smallholder farmers). The two case studies show how ICT can help to establish an efficient traceability system and improve consumers' confidence in the products. They also show that collaboration between public and private sectors is a key to success. The traceability systems facilitate improved efficiency in the management of the supply chain. At the same time, in the event of a food safety incident, the source of the problem can be more quickly identified and appropriate action taken. It is expected that traceability systems will be increasingly adopted in food-exporting countries as a strategy to improve competitiveness in the global food market.
Keywords: Q17; O31; L66; O13; 330